Prevalence of hemoglobinopathies using high-performance liquid chromatography as diagnostic tool in anemic patients of tertiary care center of Western India - Virender Singh; Amit Kumar Biswas; Ajay Kumar Baranwal; Bhushan Asthana; Tejpal Dahiya (Asian Journal of Transfusion Science)
CONTEXT: Hemoglobinopathies are the most common heterogeneous group of monogenetic disorder in the world and its prevalence varies with geographical regions. India is developing country and many studies show a significant burden of hemoglobinopathies in India. AIMS: The aim of the present study was to check the prevalence of various hemoglobinopathies in anemic subjects using high-performance liquid chromatography (HPLC) method in Pune region which has multiple ethnic population groups from all parts of India. SETTINGS AND DESIGN: The present study was conducted at the department of IH and BT on anemic patients referred from different outpatient department and Wards of the hospital and informed consent were taken from all participants. SUBJECTS AND METHODS: The present study included a total of 2698 individuals’ age ranging from 1.5 to 67 years. The HPLC test was performed using Bio-Rad D-10 analyzer once a week. RESULTS: Out of a total of 2698 cases, we found 543 (20.12%) cases with abnormal hemoglobin fractions and 2155 (79.88%) cases free from hemoglobinopathies. Out of the total hemoglobinopathies detected 250 (46%) were male and 293 (54%) were female. The major abnormality detected was beta-thalassemia trait (BTT) with 425 (15.75%) cases, followed by sickle cell disorders 58 (2.15%), HbE 38 (1.41%), hereditary persistence of fetal hemoglobin 6 (0.22%), HbD Punjab 13 (0.48%), HbD Iran 2 cases and 4 cases of compound heterozygous for HbS beta-thalassemia. Forty (1.48%) cases were detected as borderline with HbA2 level ranges from 3.6% to 3.9%. CONCLUSIONS: In our study, we found a high prevalence of hemoglobinopathies among anemic subjects. The most common disorder detected was BTT. Most of the hemoglobinopathies found in our study could be accurately quantified by HPLC which is a rapid, sensitive, and reproducible method for the detection of different hemoglobinopathies.